People with Disabilities Reality Regardless of Legal Texts - Enyier Monroy, David (Trabajo Social UNAM, 2016)
Equality, non-discrimination and freedom of movement are rights guaranteed to us by our Constitution, as well as by numerous international treaties and agreements which the Mexican State has signed and ratified. However, in reality, still outside legal texts, there are many architectural, technological and communications barriers which condition the freedom of movement of those who have some kind of disability, preventing these people from exercising their rights and as a result their social inclusion. Implementing public policies which would make it possible for them to exercise these official rights is the challenge that six million Mexicans with disabilities face, in order for them to enjoy the democratic development of our society on equal terms with all other Mexicans.